Estrategias didácticas para incentivar la comprensión lectora en estudiantes de tercer año de educación básica del Centro Educativo Capitán Moroni de la ciudad de Quevedo del periodo lectivo 2021-2022 - Baque Tumbaco, Katty Gabriela (2021)
The objective of this study was to describe didactic strategies to promote reading comprehension in third-year students of basic education from the Capitán Moroni de Quevedo educational center, through the recognition of elements that are presented in the context that surrounds them. The results show that children have a certain interest in reading, but this is not enough, because when they read, they often do it to fulfill a task or obligation, not because they like to read and go there for fun and independence. Faced with this reality, didactic strategies are proposed that help teachers to instill good readers in children, develop reading habits and at the same time improve their learning. The research is based on field work carried out with children, through the application of information gathering tools (surveys). The result is a benchmark to recommend the implementation of teaching strategies that promote interest in reading and ensure the formation of good reading habits that contribute to the comprehensive learning of children. Reading has become one of the basic skills for The development of communication is an invaluable knowledge acquisition tool that uses a process of understanding and analysis of different symbols or signs linked in order to form ideas and transmit information, through the implementation of different strategies such as: reading different types of texts, analyze texts, summarize, dramatize fables, read images among others, the students strengthened favorable skills in terms of comprehension in their different spaces.